National Identity Defense In Facing Asean Economic Community Through Curriculum Development - Jagad Aditya Dewantara; Khabibatul Fatkhi; Asep Rudi Casmana (Universitas of Muhammadiyah Makassar, 2021)
Each nation or country has a national identity that is different from another country, so that identity becomes the unique characteristic of a nation. In this era of the 21st century, the community is demanded to ready to face globalization or ASEAN Economic Community (AEC), which becomes a challenge for Indonesian people in defending nation identity when facing acculturation as a result of the free economy market so many foreigners will come to Indonesia freely. Therefore to solve that problem, it needs an effort to defend the national identity and national identity in facing AEC, so the nation's existence will keep maintained. One of them is through education. This paper aims to find out how to defend national identity through curriculum development that prevailed in Indonesia. The method used in this paper is an analytical description with a literature study that combines systematic review techniques as supporting data. National identity defense can be done through curriculum development in education by presenting or studying national identity in civic education material through the educational syllabus. Setiap bangsa atau negara memiliki identitas nasional yang berbeda dari negara lain, sehingga identitas menjadi ciri khas unik suatu bangsa. Di era abad ke-21 ini, masyarakat dituntut siap menghadapi globalisasi atau Masyarakat Ekonomi ASEAN (MEA), yang menjadi tantangan bagi masyarakat Indonesia dalam mempertahankan jati diri bangsa ketika menghadapi akulturasi sebagai akibat pasar ekonomi bebas sehingga banyak orang asing akan datang ke Indonesia dengan bebas. Oleh karena itu untuk mengatasi masalah tersebut, perlu upaya untuk mempertahankan identitas nasional dan identitas nasional dalam menghadapi MEA, sehingga eksistensi bangsa akan tetap terjaga. Salah satunya melalui pendidikan. Makalah ini bertujuan untuk mengetahui bagaimana mempertahankan identitas nasional melalui pengembangan kurikulum yang berlaku di Indonesia. Metode yang digunakan dalam makalah ini adalah deskripsi analitis dengan studi literatur yang menggabungkan teknik tinjauan review sistematis sebagai data pendukung. Pertahanan identitas nasional dapat dilakukan melalui pengembangan kurikulum dalam pendidikan dengan menghadirkan atau mempelajari identitas nasional dalam materi pendidikan kewarganegaraan melalui silabus pendidikan.